Association Between 25(ОН)D Concentration and Atopic Dermatitis and Its Severity Children Aged from 3 to 6 Years: Cross Sectional Study - Tatiana S. Kashinskaya; Natalia V. Shakhova ("Paediatrician" Publishers LLC, 2021)
Background. The association between the vitamin D provision for children and the atopic dermatitis (AD) development and severity is not clearly determined.Objective. The aim of the study was to compare 25(OH)D serum concentration in children with AD and in healthy peers with association analysis of 25(OH)D with disease severity and allergen sensibilization.Methods. The study included children aged from 3 to 6 years with AD and their healthy peers. Vitamin D provision was estimated via 25(OH)D serum concentration determined by chemiluminescent microparticle immunoassay. Vitamin D deficiency was established at 25(OH)D concentration 20 ng/ml, insufficiency - 21-29 ng/ml. Sensibilization to airborne (Dermatophagoides pteronyssinus, Dermatophagoides farinae, cat epithelium and dandruff) and food (cow's milk and chicken egg proteins) allergens was determined by IgE concentration revealed via immunofluorescence.Results. The 25(OH)D serum concentration in children with AD (n = 106) was lower than in their healthy peers (n = 40), median (interquartile range) - 26.5 ng/ml (19.0-35.3) and 32.4 ng/ml (27.9-37.5) respectively (p = 0.012). Meanwhile, vitamin D insufficiency/deficiency according to 25(OH)D concentration was revealed in more than half patients (58%) with AD and in every third child (37%) from control group (OR - 3.5, 95% CI - 1.6-7.5). It was also revealed that 25(OH)D concentration was lower in patients with moderate course of AD (in comparison to mild) as well as in children sensibilized to airborne and/or food allergens.Conclusion. The vitamin D provision in preschool children is associated with AD, its severity and the presence of sensibilization to airborne and/or food allergens.